2016
DOI: 10.1371/journal.pone.0148412
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Trans-Lamina Cribrosa Pressure Differences in Low-Teen and High-Teen Intraocular Pressure Normal Tension Glaucoma: The Korean National Health and Nutrition Examination Survey

Abstract: BackgroundTo investigate the association between estimated trans-lamina cribrosa pressure difference (TLCPD) and prevalence of normal tension glaucoma (NTG) with low-teen and high-teen intraocular pressure (IOP) using a population-based study design.MethodsA total of 12,743 adults (≥ 40 years of age) who participated in the Korean National Health and Nutrition Examination Survey (KNHANES) from 2009 to 2012 were included. Using a previously developed formula, cerebrospinal fluid pressure (CSFP) in mmHg was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
1
28
0
1
Order By: Relevance
“…Using 2010–2012 KHANES data, we previously demonstrated that in the low‐teen IOP group, OAG was more significantly associated with hypertension and taking antihypertensive medication, while in the high‐teen IOP group, a higher estimated trans‐lamina cribrosa pressure difference was associated with OAG prevalence (Lee et al. ). The findings of this study were consistent with the results from prior studies, in which low‐teen OAG subjects were more likely to have vascular and metabolic comorbidities than were subjects with high‐teen OAG, and further add to the current hypothesis that vascular factors are more closely related to OAG with low‐teen baseline IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Using 2010–2012 KHANES data, we previously demonstrated that in the low‐teen IOP group, OAG was more significantly associated with hypertension and taking antihypertensive medication, while in the high‐teen IOP group, a higher estimated trans‐lamina cribrosa pressure difference was associated with OAG prevalence (Lee et al. ). The findings of this study were consistent with the results from prior studies, in which low‐teen OAG subjects were more likely to have vascular and metabolic comorbidities than were subjects with high‐teen OAG, and further add to the current hypothesis that vascular factors are more closely related to OAG with low‐teen baseline IOP.…”
Section: Discussionmentioning
confidence: 99%
“…The authors caution, however, that further experimental investigations and longitudinal prospective clinical studies are required to overcome the methodological weaknesses of the current studies, concerns echoed by Pircher and Killer [138]. Since this time, the Beijing intracranial and intraocular pressure (iCOP) reported a positive association between TLPD (calculated from LP-CSFP) and visual field defects in POAG patients [77] and a population-based study from the Korean National Health and Nutrition Examination Survey (KNHANES) found that TLPD (calculated from estimated CSFP values) was significantly associated with HT-NTG [104]. …”
Section: Mechanisms Of Rgc and Axonal Deathmentioning
confidence: 96%
“…Although non-invasive methods would be preferable due to the risk of complications with the invasive ones, the indirect methods are not considered to be sufficiently reliable for clinical practice [ 37 40 ]. Still, conclusions on TLCPD are based on studies that used indirect methods to estimate TLCPD [ 70 , 71 , 73 , 74 , 76 ].…”
Section: Clinical Implications Of Tlcpdmentioning
confidence: 99%
“…Similarly, Lee et al used the same mathematical formula to estimate ICP. They found an association between higher TLCPD and NTG with high-teen IOP values, but the same was not true for low-teen NTG patients [ 74 ].…”
Section: Clinical Implications Of Tlcpdmentioning
confidence: 99%